If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 3 = 7x + -105 Reorder the terms: 3 + -5x = 7x + -105 Reorder the terms: 3 + -5x = -105 + 7x Solving 3 + -5x = -105 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 3 + -5x + -7x = -105 + 7x + -7x Combine like terms: -5x + -7x = -12x 3 + -12x = -105 + 7x + -7x Combine like terms: 7x + -7x = 0 3 + -12x = -105 + 0 3 + -12x = -105 Add '-3' to each side of the equation. 3 + -3 + -12x = -105 + -3 Combine like terms: 3 + -3 = 0 0 + -12x = -105 + -3 -12x = -105 + -3 Combine like terms: -105 + -3 = -108 -12x = -108 Divide each side by '-12'. x = 9 Simplifying x = 9
| v(x)=x(40-2x)(30-2x) | | 11y=6+10y | | 5(3-2x)=-35 | | -3x-3(2x)=21 | | y(4y-7)=0 | | 2x-40=25 | | Y=-x^2-5.5x+1 | | -32d+28=18 | | 1/8x-5/2 | | x+1=-59-5x | | -32+28=18 | | 39=14-5m | | X+.0665X= | | 3x-6=-17+4x | | 12z-21=3z+9 | | 1/2y-15=12 | | 8+6x=-6x-100 | | 19=j+4 | | 4a-11=13 | | 38y+16-8=33 | | 1x(1x(45-40))= | | 7y+27=125 | | 4=24-56 | | (x+7)(x-1)=(2x+3)(x-1) | | -q=x-3 | | 16t^2=2704 | | 195=2x-7(-x-15) | | 31y-12=360 | | 8n-8=24 | | (5x^2-7x-8)+(2x^2-3x+7)-(x^2-4x-3)= | | -x-5=q | | 7x-3=5x/2 |